Double magnets causing double perforations-a case report - Inugala, Anusiri (International Surgery Journal, 2020)
Magnets are unusual gastrointestinal foreign bodies. Ingestion of multiple magnets may lead to serious complications including bowel perforation. Presenting the case of an 11-year-old girl who ingested 2 singing magnets. The patient presented with a history of pain abdomen and bilious vomiting and constipation of one day duration, 20 days after ingestion of the magnets. On examination there was distension of abdomen and severe tenderness all over the abdomen along with rigidity. Abdominal radiograph showed the presence of foreign bodies in the abdomen. In view of features of peritonitis, the patient was taken up for an exploratory laparotomy. Intraoperatively two perforations were found, one in the jejunum and the other in the ileum. The perforations were caused due to the pressure necrosis caused by the presence of magnets in different loops of the bowel. The perforations were closed. Post-operative period was uneventful. In conclusion, it is important to be aware of the problems that can be caused in cases of multiple magnet ingestion and to intervene at the earliest to prevent further complications.